2004
DOI: 10.1097/01.ju.0000112782.00417.5e
|View full text |Cite
|
Sign up to set email alerts
|

Nonsecretory Intestinocystoplasty: A 10-Year Experience

Abstract: Based on our study we conclude that demucosalized intestine is a safe alternative for bladder augmentation and can be used for the same indications as total bowel segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The salient feature of our technique is the placement of an intraluminal Foley catheter with the balloon distended to facilitate dissection. This was reported by Lima et al 11 claiming that this allowed the surgeon to enter the correct plane preventing intestinal regrowth. We entirely agree with their observation and ourselves found that the Foley balloon behaved like a “mucophilic” device attracting the mucosa to it.…”
Section: Commentmentioning
confidence: 81%
See 2 more Smart Citations
“…The salient feature of our technique is the placement of an intraluminal Foley catheter with the balloon distended to facilitate dissection. This was reported by Lima et al 11 claiming that this allowed the surgeon to enter the correct plane preventing intestinal regrowth. We entirely agree with their observation and ourselves found that the Foley balloon behaved like a “mucophilic” device attracting the mucosa to it.…”
Section: Commentmentioning
confidence: 81%
“…We did not have any case of obstruction in this study. Lima et al 11 removed the mucosa per rectum and excised it preoperatively.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al later reported on their clinical experience in 25 patients undergoing ileal seromuscular cystoplasty using the same silicone mold technique (99). It is not clear if any of the patients underwent concomitant procedure at the time of augmentation.…”
Section: Urothelial Preserving Augmentation Techniquesmentioning
confidence: 99%
“…Studies using intravesical silicone balloons after autoaugmentation showed an increase of 329% in bladder capacity and a sevenfold increase in compliance. 6 The present study assessed the different surgical techniques for laparoscopic bladder autoaugmentation with and without the use of the intravesical silicone balloon in dogs so that future experiments can better evaluate this promising procedure.…”
Section: Introductionmentioning
confidence: 99%